Serpent gate a Kevin Kerney novel - McGarrity, Michael (New York, NY : Scribner, 1998)
Assigned to lead the investigation of a multi-million-dollar art theft from New Mexico's state capitol building, Santa Fe policeman Kevin Kerney finds himself face to face with an old enemy with ties to the Mexican government.
72941
Keywords: Police -- Fiction. -- New Mexico -- Santa Fe